Analisis Keterampilan Teknik Bermain Sepak Bola Pada Pertandingan Final Copa America Argentina Vs Colombia Tahun 2024 - Ach. Fathur Rozy; Achmad Widodo (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This study aims to analyse the skills of the players of the Argentine and Colombian national teams in the 2024 Copa America final match, focusing on various aspects, including passing, shooting, control, and dribbling. Data collection was conducted through direct tests involving amateur soccer players competing at the national level. The analysis results indicate significant variations in the physical conditions and skills between players. The objective of this research is to understand the effectiveness of Argentina and Colombia during the 2024 Copa America Final, which ended with a score of 1-0 in Favor of Argentina, crowning them as champions. The research methodology used was descriptive quantitative. The data sources for this study were obtained from the video recording of the 2024 Copa America Final match. The results showed that Argentina achieved 378 accurate passes (82%), six successful shots on target (54%), four successful dribbles (40%), and 364 successful controls (93%). The conclusion drawn indicates that Colombia's playing techniques should have been more superior but failed to breach Argentina's defens. Both teams played exceptionally well, as reflected in the collected data, but differences were found in their formations. An analysis of the Colombian National Team's playing performance concluded that their techniques were good but not maximally utilized. The opportunities they had will serve as material for the team's evaluation moving forward.